(untitled) (Plant Bulletin, 2025)
Bacterial blight of cotton, caused by Xanthomonas citri pv. malvacearum (Xcm) is a major threat to cotton production in Pakistan. The pathogenicity of Xcm was evaluated against different cotton varieties to assess the susceptibility of local cotton varieties against the bacterial pathogen. Furthermore, multiple management strategies were performed in the field conditions to find out the suitable management strategy against the bacterial blight in Dera Ghazi Khan. The bacterium was isolated from affected cotton leaves, which produced yellow, mucoid colonies on nutrient agar media, confirming its identity as Xanthomonas using physical features and Gram staining. Three cotton varieties (BS-313, FH-333, and FH-Lalazar) were tested for pathogenicity, and the results showed that all were susceptible. FH-Lalazar had the highest disease severity (70.91%), followed by BS-313 (61.49%) and FH-333 (58.04%). Neem (Azadirachta indica) and moringa (Moringa oleifera) extracts were applied at a 15% concentration as Botanical extracts, and both decreased the severity of disease in comparison to the untreated plants. Neem extract was more effective (lowering the disease severity of the variety FH-333 to 49.22%) as compared to moringa extract. Kasugamycin and copper oxychloride decreased the severity to 10.45% in FH-333, demonstrating the superiority of chemical control. Tebuconazole and trifloxystrobin also reduced the disease severity, but not as much as kasugamycin. Statistical analysis (ANOVA and LSD test, p < 0.05) confirmed that the differences among treatments were significant, with chemical treatments showing the highest efficacy in reducing disease severity. These findings indicate that none of the tested cultivars exhibited resistance, and botanical extracts showed promise as environmentally friendly substitutes, although chemical treatments remain the most dependable option. For the sustainable management of bacterial blight in cotton under local conditions, an integrated strategy combining plant extracts, resistant varieties, and selective chemical use is advised.